Accelerated mitochondrial evolution and asymmetric fitness of hybrids contribute to the persistence of Helix thessalica in the Helix pomatia range - Korábek, Ondřej; Hausdorf, Bernhard (Molecular ecology, 2024)
Interbreeding and introgression between recently diverged species is common. However, the processes that prevent these species from merging where they co-occur are not well understood. We studied the mechanisms that allowed an isolated group of populations of the snail Helix thessalica to persist within the range of the related Helix pomatia despite high gene flow. Using genomic cline analysis, we found that the nuclear gene flow between the two taxa across the mosaic hybrid zone was not different from that expected under neutral admixture, but that the exchange of mtDNA was asymmetric. Tests showed that there is relaxed selection in the mitochondrial genome of H. thessalica and that the substitution rate is elevated compared to that of H. pomatia. A lack of hybrids that combine the mtDNA of H. thessalica with a mainly (>46%) H. pomatia genomic background indicates that the nuclear-encoded mitochondrial proteins of H. pomatia are not well adapted to the more rapidly evolving proteins and RNAs encoded by the mitochondrion of H. thessalica. The presumed reduction of fitness of hybrids with the fast-evolving mtDNA of H. thessalica and a high H. pomatia ancestry, similar to 'Darwin's Corollary to Haldane's rule', resulted in a relative loss of H. pomatia nuclear ancestry compared to H. thessalica ancestry in the hybrid zone. This probably prevents the H. thessalica populations from merging quickly with the surrounding H. pomatia populations and supports the hypothesis that incompatibilities between rapidly evolving mitochondrial genes and nuclear genes contribute to speciation.
Keywords: Mitochondria; molekulární evoluce; tok genů; populační genetika; Hybridization, Genetic; genom mitochondriální; mitochondriální DNA; Evolution, Molecular; Genetics, Population; Genome, Mitochondrial; DNA, Mitochondrial; Gene Flow; mitochondrie; Genetic Fitness; zvířata; Helix (hlemýždi); hybridizace genetická; land snail; Darwin's Corollary; hybrid zone; genetická zdatnost; speciation; Animals; mitonuclear incompatibility; selekce (genetika); Selection, Genetic; genomic cline; Helix, Snails